مستوى التحصيل في اللغة الفرنسية في ظل تدريس اللغة الانجليزية لدى تلاميذ السنة الثالثة ابتدائي (دراسة ميدانية ببعض ابتدائيات بلدية قمار–الوادي-) - برحومة, سميرة (University of Eloued جامعة الوادي, 2023)
تهدف هذه الدراسة الى معرفة مستوى التحصيل في اللغة الفرنسية في ظل ادراج اللغة الانجليزية لدى تلاميذ السنة الثالثة ابتدائي. واعتمدنا على المنهج الوصفي التحليلي كونه ملائم لهذه الدراسة. وجمعنا البيانات بالاعتماد على سجل نتائج الفرنسية لدى عينة من 62 تلميذ من ابتدائيات الخنساء والنجاح بقمار ولاية الوادي للسنة الدراسية 2021/2022 والسنة الدراسية الحالية 2022/2023 بطريقة عشوائية وبعد تحليل ومناقشة المعلومات والبيانات توصلنا الى:  ان مستوى تحصيل اللغة الفرنسية مرتفع لدى أفراد العينة.  لا توجد فروق في مستوى التحصيل لدى تلاميذ السنة الثالثة ابتدائي في ظل ادراج اللغة الانجليزية على العينة المدروسة. Abstract This study aims to know the level of achievement in the French language in light of the inclusion of the English language among third-year primary school students. We relied on the analytical descriptive approach, as it is suitable for this study. And we collected data based on the French results record for a sample of 62 students in the elementary schools of Al-Khansa and An-Najah in gambling in El-OUED state for the academic year 2021/2022 and the current academic year 2022/2023 in a random manner, and after analyzing and discussing the information and data, we concluded that there were:  _The level of the french language is ligh among the respondents.  No differences in the level of achievement among the students of the year the third primary in light of the inclusion of the English language on the studied sample.
تخصص علم نفس